A Novel Open-Framework Cu-Ge-Based Chalcogenide Anode Material for Sodium-Ion Battery. (27th December 2017) - Sun, Quan; Fu, Lin; Shang, Chaoqun
Abstract : Open-framework chalcogenides are potential electrode materials for sodium-ion batteries (SIBs) due to their architectures with fast-ion conductivity. Herein, we report on the successful synthesis of open-framework Cu-Ge-based chalcogenides [Cu8 Ge6 Se19 ](C5 H12 N)6 (CGSe) and the research of their energy storage application as SIB anodes for the first time. As a result, the CGSe anode exhibited good electrochemical performances such as high reversible capacity (463.3 mAh g −1 ), excellent rate performance, and considerable cycling stability. Our exploration not only develops a promising electrode material for SIBs, but also extends the application of open-framework chalcogenides.